Effects of informal learning on work engagement. Issue 7 (4th November 2019) - Susomrith, Pattanee; Coetzer, Alan
Abstract : Purpose: The purpose of this paper is to explore the relationships between task-based and interactional informal learning practices in small professional services firms and the moderating role of proactivity in the relationship. Design/methodology/approach: Job demand-resources theory was used to develop theoretical arguments for a link between informal learning and work engagement. Data were collected from 203 employees in professional services firms and analysed using structural equation modelling. Findings: Analysis of the data showed that opportunities to learn through task-based learning processes and through interactions with supervisors and colleagues were positively related to employees' levels of work engagement. Furthermore, the strength of relationships between these informal learning practices and work engagement was influenced by employees' proactivity. Research limitations/implications: The limitations pertain to the non-random sampling procedure, cross-sectional nature of the study and the use of self-report measures. These limitations were mitigated by employing rigorous analytical procedures. Practical implications: The results suggest that managers are able to influence the quantity and quality of informal workplace learning through strategies such as selecting employees who have a propensity for proactive behaviour, encouraging proactive behaviour, enabling experimentation and reflection and fostering positive interpersonal relations. Originality/value: The study links two streams of research that have seemingly not been connected previously. The results suggest that small firms are sites with abundant potential for development of employees' knowledge and skills and the associated experiences of work engagement.